The interactions between the Republic of Kazakhstan and the countries of the Persian Gulf: the constructivist approach - А.М. Исалиева; А.Ж. Турханова (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
The basis for the development of multilateral cooperation between Kazakhstan and the countries of the Persian Gulf primarily comes from an important Islamic component of Kazakhstan society. The attraction of financial assistance from the Arab States in favor of resolving the economic issues of the country of Kazakhstan’s diplomacy was possible thanks to cultural and civilizational communities. Therefore, in order to implement the strategic objectives of foreign policy formulated by the head of state aimed at strengthening the republic’s position in the international arena, Kazakhstan is determined to further develop political, economic, cultural and humanitarian cooperation with the countries of the Persian Gulf. The aim of this article is identify the role of the Islamic component in the relations of the Republic of Kazakhstan with the countries of the Persian Gulf. The constructivist approach is used as a theoretical and conceptual basis. Also methods of comparative and content-analysis were used. The author gives the views of Arab and Kazakstani experts about specifics of the relationship between the parties. The obtained results make it possible to trace the significance of civilizational closeness, thanks to which the foundation of mutually beneficial cooperation of the parties is laid.